Trimethylamine N-oxide, a gut microbiota-dependent metabolite of choline, is positively associated with the risk of primary liver cancer: a case-control study - Liu, Zhao-Yan; Tan, Xu-Ying; Li, Qi-Jiong; Liao, Gong-Cheng; Fang, Ai-Ping; Zhang, Dao-Ming; Chen, Pei-Yan; Wang, Xiao-Yan; Luo, Yun; Long, Jing-An; Zhong, Rong-Huan; Zhu, Hui-Lian (Nutrition & metabolism, 2018)
Evidence has suggested a potential link exists between trimethylamine-N-oxide (TMAO), a choline-derived metabolite produced by gut microbiota, and some cancers, but little is known for primary liver cancer (PLC). A case-control study was designed including 671 newly diagnosed PLC patients and 671 control subjects frequency-matched by age (±5 years) and sex, in Guangdong province, China. High-performance liquid chromatography with online electrospray ionization tandem mass spectrometry (HPLC-MS/MS) was used to measure serum TMAO and choline. The associations between these biomarkers and PLC risk were evaluated using logistic regression models. Serum TMAO concentrations were greater in the PLC group than the control group ( = 0.002). Logistic regression analysis showed that the sex- and age-adjusted odds ratio (OR) and (95% confidence interval [CI]) was 3.43 (2.42-4.86) when comparing the top and bottom quartiles (Q4 vs Q1). After further adjusting for more selected confounders, the OR (95% CI) remained significant but was attenuated to 2.85 (1.59-5.11) (Q4 vs Q1). The multivariable-adjusted ORs (95% CIs) across quartiles of choline were 0.35-0.15 ( < 0.001). Higher serum levels of TMAO were associated with increased PLC risk. The association was stronger in those with lower serum levels of choline. Additional large prospective studies are required to confirm these findings. This study was registered at clinicaltrials.gov as NCT 03297255.